Headteachers Conflict Management Styles and Teachers Job Satisfaction in Malaysian Primary Schools - Mohd Izham; Nurul Sahadila; Aida Hanim (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2017)
The purpose of this study was to investigate the conflict management styles among head teachers and the relationships between the styles and teachers job satisfaction. The study also examined the head teachers conflict management styles and teachers job satisfaction based on the demographic characteristics. A questionnaire was administered to 120 respondents in 5 primary schools in the district of Tampin, Malaysia. Descriptive and Manova statistics were used to examine the levels and differences of conflict management styles used among head teachers and teachers job satisfaction in terms of their demographic characteristics. The findings showed that the head teachers used all the five conflict management styles: cooperating style, adapting style, compromising style, bargaining style, and problem-solving style. Most head teachers preferred cooperating style as compared to bargaining style. Further, the findings showed that there was no difference for all the five conflict management styles in relation to the head teacher demographic characteristics. However, the findings showed that there was a significant difference for teachers job satisfaction in terms of years of service and no difference for teachers job satisfaction in terms of other demographic characteristics. Implications for all policymakers to improve future policy related to leadership training for all head teachers in schools were discussed.